2011
DOI: 10.1149/1.3633684
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) ALD of Thin Films for Lithium-Ion Batteries

Abstract: Atomic layer deposition (ALD) technique is a thin film deposition method that provides highly conformal films on 3D structured supports, including powder materials. The technique relies on sequential self-limiting gas-to-surface reactions which enable control of thin film depositions even down to the atomic level on complex surface geometries. Even if ALD technique has been used in the semiconductor industry in production scale for several years now, there are rather few reports on ALD of battery materials. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In this section emphasis is given to potential solid electrolyte materials, as these are generally considered the most difficult materials to deposit. For a more thorough review of this subject, both review articles and books are available [71][72][73][74][75][76][77][78][79]. In recent years, ALD has also been studied extensively as a method to modify the interfaces between the electrodes and the electrolyte by forming an artificial SEI-layer [75,80,81].…”
Section: Atomic Layer Deposition Of Conventional Lithium-ion Battery mentioning
confidence: 99%
“…In this section emphasis is given to potential solid electrolyte materials, as these are generally considered the most difficult materials to deposit. For a more thorough review of this subject, both review articles and books are available [71][72][73][74][75][76][77][78][79]. In recent years, ALD has also been studied extensively as a method to modify the interfaces between the electrodes and the electrolyte by forming an artificial SEI-layer [75,80,81].…”
Section: Atomic Layer Deposition Of Conventional Lithium-ion Battery mentioning
confidence: 99%
“…[15][16][17] To our knowledge, there are only preliminary reports on Li x Ti y O z deposition by ALD. [18][19][20] In the present study we combined the TiO 2 and Li 2 O-LiOH binary ALD processes to prepare the Li x Ti y O z ternary material. For the TiO 2 subcycle we studied the effect of alkoxide and chloride based chemistries on Li x Ti y O z growth.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, its applications to secondary batteries have attracted extensive research attention. 14,15 Some studies have also reported on the use of Li 3 PO 4 for solid electrolytes. 16,17 However, in the case of LiPON, which has a higher conductivity than Li 3 PO 4 , deposition must be performed with a constant composition ratio for the four constituent elements: Li, P, O, and N. Plasma assistance is also considered necessary 18 because of the difficulty of nitriding at low temperatures.…”
mentioning
confidence: 99%